Chlamydia trachomatis Lipopolysaccharide Evades the Canonical and Noncanonical Inflammatory Pathways To Subvert Innate Immunity - Chunfu Yang (American Society for Microbiology, 2019)
ABSTRACT Chlamydia trachomatis is the most common bacterial cause of sexually transmitted infections. C. trachomatis sexually transmitted infections are commonly asymptomatic, implying a pathogenic strategy for the evasion of innate inflammatory immune responses, a paradox as the C. trachomatis outer membrane contains lipopolysaccharide (LPS), a known potent agonist of inflammatory innate immunity. Here, we studied the ability of chlamydial LPS to activate the proinflammatory canonical and noncanonical inflammasome pathways in mouse bone marrow-derived macrophages (BMDM). We show, in comparison to Escherichia coli LPS, that C. trachomatis LPS-treated BMDM produce significantly less IL-6, TNF, and type I interferon mRNA, indicating that downstream signaling through the canonical TLR4 myddosome and triffosome pathways was blocked. We confirmed this in C. trachomatis LPS-treated BMDM by showing the lack of NF-κB and IRF3 phosphorylation, respectively. Interestingly, C. trachomatis LPS bound CD14 and promoted its endocytosis; however; it did not promote efficient TLR4/MD-2 dimerization or endocytosis, known requirements for myddosome and triffosome signaling pathways. We further found that transfection of BMDM with C. trachomatis LPS did not cause pyroptotic cell ballooning, cytotoxicity, or IL-1β secretion, all characteristic features of noncanonical inflammasome activation. Western blotting confirmed that cytosolic C. trachomatis LPS failed to signal through caspase-11, as shown by the lack of gasdermin D, caspase-1, or IL-1β proteolytic cleavage. We propose that chlamydiae evolved a unique LPS structure as a pathogenic strategy to avoid canonical and noncanonical innate immune signaling and conclude that this strategy might explain the high incidence of asymptomatic infections. IMPORTANCE Chlamydia trachomatis is the most common bacterial cause of sexually transmitted infections (STI). C. trachomatis STI are commonly asymptomatic, implying a pathogenic strategy for the evasion of innate inflammatory immune responses, a paradox as the C. trachomatis outer membrane contains lipopolysaccharide (LPS), a known potent agonist of inflammatory innate immunity. Here, we found that C. trachomatis LPS is not capable of engaging the canonical TLR4/MD-2 or noncanonical caspase-11 inflammatory pathways. The inability of C. trachomatis LPS to trigger innate immunity inflammatory pathways is related to its unique fatty acid structure. Evolutionary modification of the LPS structure likely evolved as a pathogenic strategy to silence innate host defense mechanisms. The findings might explain the high incidence of asymptomatic chlamydial genital infection.